2011
DOI: 10.1186/1475-2875-10-150
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system exposure of next generation quinoline methanols is reduced relative to mefloquine after intravenous dosing in mice

Abstract: BackgroundThe clinical use of mefloquine (MQ) has declined due to dose-related neurological events. Next generation quinoline methanols (NGQMs) that do not accumulate in the central nervous system (CNS) to the same extent may have utility. In this study, CNS levels of NGQMs relative to MQ were measured and an early lead chemotype was identified for further optimization.Experimental designThe plasma and brain levels of MQ and twenty five, 4-position modified NGQMs were determined using LCMS/MS at 5 min, 1, 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In the present study, JPC-3210 was found to concentrate in the brain, with a mean Ϯ SD brain tissue-to-plasma ratio (Kp) of 4.6 Ϯ 1.4 at 2 h, 5.0 Ϯ 0.7 at 24 h, and 6.7 Ϯ 1.3 at 72 h after oral administration of JPC-3210 in mice, which are in accord with its relatively high apparent volume of distribution and lipophilic properties. In comparison to JPC-3210, mefloquine, a drug that can cause neurological disturbances in some individuals due to its highly lipophilic properties and extensive distribution to tissues, has a Kp of 3.9 at 24 h after intravenous administration of the drug in mice (18). However, Kp is based on a crude homogenization of brain tissue and as such ignores the compartmentalization of the brain.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, JPC-3210 was found to concentrate in the brain, with a mean Ϯ SD brain tissue-to-plasma ratio (Kp) of 4.6 Ϯ 1.4 at 2 h, 5.0 Ϯ 0.7 at 24 h, and 6.7 Ϯ 1.3 at 72 h after oral administration of JPC-3210 in mice, which are in accord with its relatively high apparent volume of distribution and lipophilic properties. In comparison to JPC-3210, mefloquine, a drug that can cause neurological disturbances in some individuals due to its highly lipophilic properties and extensive distribution to tissues, has a Kp of 3.9 at 24 h after intravenous administration of the drug in mice (18). However, Kp is based on a crude homogenization of brain tissue and as such ignores the compartmentalization of the brain.…”
Section: Resultsmentioning
confidence: 99%
“…This observation, suggesting the occurrence of some synergy between the in vitro effects of mefloquine and amitriptyline, led us to investigate whether a similar interaction might also occur in vivo . Indeed, mefloquine appeared especially relevant for such studies because it crosses the blood brain barrier46. Furthermore, its pharmacological profile indicates a relatively good selectivity as a Cx channel inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing free to whole mouse brain concentrations following a single i.v. dose, Dow et al, 2011) calculated a ratio of 4.9/1807, or 0.0027, with a whole brain concentration of about 4μM, and about 18 nM free brain mefloquine in mice. However, soldiers taking the drug prophylactically and who were killed in the line of duty had brain levels of 8.7 to 14 mg/kg (Jones et al, 1994).…”
Section: Discussionmentioning
confidence: 99%